Peran sanksi administrasi dalam menegakkan kepatuhan perpajakan di indonesia - Husnaini, Nafa Arinal (Maliki Interdisciplinary Journal, 2025)
One of the main pillars supporting a nation’s economic growth is taxation. For an efficient tax system to function, taxpayer compliance is essential. Penalties, including fines, interest, and more severe measures, are used in Indonesian tax administration not only as a form of punishment but also as a means of enforcing discipline and encouraging taxpayers to abide by applicable laws. The various forms of tax administration fines, their legal foundation, and how the processes for enforcing them help taxpayers comply better are all covered in this article. Since administrative fines entail strict regulations and enforcement, it is anticipated that they will improve the fairness, responsibility, and orderliness of the tax environment.